RELIABILITY BASED ROBUIST DESIGN OPTIMIZATION OF WIND TURBINE GEAR BOX BASED ON DYNAMICS - WANG ChunGuang (Jixie qiangdu)
In order to meet the design requirements of large wind turbine gearbox with high reliability,good dynamic characteristics and high robustness,based on the system dynamic model and considering the correlation among the failure modes,a multi-objective optimization design mathematical model is developed from the perspective of system dynamics,reliability,robustness and volume. An engineering example is present,the simulated annealing particle swarm optimization（ PSO） and interior penalty function method are used to solve the problem. The results show that the optimized design method and optimized design parameters can significantly improve the dynamic characteristics,reliability and robustness,and reduce the volume in the multi-stage transmission system of the load split type wind power increasing box.